FAKTOR-FAKTOR PENTING UNTUK KEEFEKTIFAN STANDAR PEMERIKSAAN KEUANGAN NEGARA (SPKN) DALAM PENGELOLAAN KEUANGAN NEGARA YANG EFISIEN: PEMIKIRAN BERKAITAN DENGAN PENYUSUNAN SPKN BADAN PEMERIKSA KEUANGAN - AINUN NA'IM (Jurnal Bisnis dan Akuntansi, 2006)
This paper discuss the draft of State Finance Auditing Standards (Standar Pemeriksaan Keuangan Negara (SPKN). The objectives of the analysis is to contribute to the efforts to develop efficient and effective government auditing system and process. The efficient and effective auditing system is one that be able to support the efficient and effective government in creating efficient bureaucracy and in developing the economy. This paper may also socialize the standards and efforts to improve the role of the Board of State Finance Audit (Badan Pemeriksa Keuangan). The SPKN draft uses a number of references from previous and existing auditing standards in the United States and that provided by the international institutions, which is appropriate for the efficiency of the process. However, the unique social, economic and regulatory situation of Indonesia should be considered in developing the govermental auditing standards for Indonesia. The transitional nature of laws and regulations such as those with regard to decentralization and autonomy, deregulations of certain industry, and privatization are too worthy for not to be considered. Auditing standards are fundamental guidelines for auditors to maintain their ethical values and to achieve the objectives of the auditing. The process should also refers to certain criteria for financial accountability i.e. generally accepted accounting standards. For those reason, the SPKN needs to state explicitly and strongly the importance of ethical values to be complied and the Governrnental Accounting Standards. This paper also address other important issues such as the need for more detailed specific industry auditing guidance and applicability of the standards.